A Study of the Relationship between Locus of Control and Self-monitoring to Resilience in Students - Shanava, Ina; Gergauli, Giorgi (European Scientific Journal, ESJ, 2023)
A person may experience both positive and negative stress, which is mainly associated with a wide range of negative consequences, such as a decrease in well-being, an increase in diseases, post-traumatic stress, anxiety, and depression disorders. High stress in a person does not always develop these negative results. According to latest researches and studies, most people are exposed to stress, and developing resilence is the main factor in order to cope with the unpredictable environment (Troy & Mauss, 2011). The ability to disengage from negative stimuli and feelings is an important protective factor against long-term negative results. Resilience represents the ability of a person to cope with life’s difficulties and is a multidimensional characteristic which varies by context, age, gender, culture, and individual life (Felicia et al., 2021). According to contemporary approaches, resilience is a personal trait that helps a person to adapt and cope with traumatic experience. Psychological component of resilience means that a person maintains psychological health without any trauma and stressors, .while behavioral component of resilience means maintenance of self-effectiveness and aspiration towards goals (Kamushadze, 2021). One of the components of resilience at the individual level is identified as self-control, which is an aspect of behavior control and is often viewed as willpower and the ability to control impulses. In a psychological sense, self-control refers to emotions and the initiation or modification of emotional reactions through cognitive processes. The locus of control is also considered to be a factor that has a significant influence on the formation of resilience. According to Rotter, people differ from each other according to the localization of control over events. This difference can be described as internal and external poles. Internal people believe that everything that happens in their lives depends only on their personal qualities, purposefulness, abilities, and competence. External people strongly believe that their lives are controlled by outside forces, and their success or failure is the fault of randomness, other people, and so on., This paper therefore focuses on determining the relationship between the locus of control and self-monitoring to resilience among undergraduate, graduate, and doctoral students. Internal-External Locus of Control Scale (I-E Scale), Self – Monitoring Scale, and Brief Resilience Scale (BRS) were used in this study. Based on the analysis of the results, it was revealed that self-ownership is related to resilience and locus of control, and the latter is negatively related to resilience. Differences were analyzed by demographic characteristics.